Evolution of extensive neo-sex chromosomes and PAR shift in Agapornis lovebirds (Supporting files, FISH raw data) - Haoran Luo (16515177) (2025)
The probe sequences and raw images of the Oligo-FISH experiments are presented in Figures 3D and supplementary Figures. Each FISHraw sub-folder includes: One chromosomes stained with DAPI (*C001T001). Two Fluorescent signals of the probes (Green *C002T001 for Old_Z-probe1 and red *C003T001 for chr7-probe2). One merged result of the probe signal and DAPI signal (*T001).